Nilai-Nilai Pendidikan Agama Islam dalam Sinetron Ustad Milenial - Oktaviani Oktaviani; H. Abu Bakar; Ilham Fahmi (Peneliti.net, 2021)
Soap operas are spectacles that are in great demand by the wider community, especially teenagers, but in this millennial era, soap operas only present the negative side rather than instilling values in it. This is what motivates the author to study this problem. Then, this study aims to find out the description of the soap opera Ustad Millennial, then the soap opera show that can foster the values of Islamic religious education for the millennial generation, then the values of Islamic religious education contained in the soap opera Ustad Millennial. The method used in this study is a qualitative method, this type of research is a qualitative literature (library research). Then the subject of this research is the soap opera Ustad Millennial broadcast on the WeTv platform. The research instrument used is data collection techniques by means of documentation. The data analysis technique used is content analysis technique. The results of this literature research show that there are many values of Islamic religious education contained in the soap opera Ustad Millennial which includes the value of aqidah/faith, moral values and worship values.